Training the trainers and disseminating information: a strategy to educate health professionals on epilepsy Capacitações e multiplicadores: uma estratégia para educação de profissionais da área de saúde na epilepsia - Paula T. Fernandes; Ana L.A. Noronha; Josemir W. Sander; Gail S. Bell; Li M. Li (Arquivos de Neuro-Psiquiatria)
PURPOSE: To evaluate the knowledge, attitudes and perceptions of epilepsy in primary care system health professionals prior to and after an educational intervention. METHODS: Educational interventions were delivered to three groups of people with an interest in epilepsy: 1. Information courses for physicians (241 subjects); 2. Social re-integration course for health professionals and community leaders (631 subjects); 3. "Training the Trainers" Course for physicians (11 subjects). The whole program is flexible and can be tailored for local or regional needs. For the evaluation of this process, health professionals completed a quantitative and qualitative questionnaire to assess their knowledge, attitudes and perception (KAP) of epilepsy prior to the training (pre-test) and 6 months after it (post-test). RESULTS: Comparison of knowledge scores prior to (mean=55.8, standard deviation=14.0) and after (mean=71.5, standard deviation=12.0) the intervention showed that physicians had improved knowledge after the training (t-test=7.8, p<0.001). The same pattern occurred with the health professionals: the knowledge score prior to (mean=22.3, standard deviation=12.5) and after (mean=36.6, standard deviation=12.5) the intervention showed that health professionals had improved knowledge after the training (t-test=12.4, p<0.001). Improvements in attitudes and perception also occurred after the courses. DISCUSSION: Training courses can promote increased knowledge, attitude and perception in a cost effective way in the primary care setting. However, a continuous education program is required to correct oversights and to improve the management of people with epilepsy. OBJETIVO: Avaliar conhecimentos, atitudes e percepção sobre epilepsia de profissionais da saúde do sistema de atenção básica antes e depois de curso de capacitação. MÉTODO: Cursos de capacitação foram realizados em três grupos de profissionais de saúde: 1. cursos de capacitação para médicos (241 sujeitos); 2. cursos de inserção social para agentes comunitários de saúde (631 sujeitos); 3. cursos de replicadores para médicos (11 sujeitos). O programa de capacitação foi adaptado para as condições de cada local. Para avaliar o processo, foram aplicados questionários a respeito do seu conhecimento, sua atitude e percepção perante à epilepsia (KAP) antes dos cursos (pré-teste) e após a intervenção (pós-teste). RESULTADOS: A comparação feita a respeito do conhecimento com médicos mostrou que os mesmos melhoram seu conhecimento com os cursos (pré-teste: nota média=55.8; DP=14,0) vs. pós-teste: nota média=71,5; DP=12,0; t-test=7,8; p<0,001). O mesmo padrão ocorreu com os agentes comunitários de saúde: pré-teste: nota média=22.3; DP=12,5) vs. pós-teste: nota média=36,6; DP=12,5; t-test=12,4; p<0,001. Com relação a atitudes e percepção, foram observadas melhoras significativas depois da realização dos cursos. DISCUSSÃO: Os cursos de capacitação promovem melhoras no conhecimento, atitude e percepção, com baixo custo e de maneira efetiva, no sistema básico de saúde. Entretanto, um programa de educação continuada deve existir para que consiga corrigir os erros e melhorar o tratamento das pessoas com epilepsia.